Morphological Evidence for a Subpopulation Selection Effect by Estrogen and Antiestrogen Treatments in the Heterogeneous MCF-7 Cell Line - Jacqueline Palmari; France Wallet; Julien Berard; Yolande Berthois; Pierre Marie Martin; Christophe Dussert (Analytical Cellular Pathology)
Recently, we developed a method to quantitatively study tumour cell heterogeneity in terms of both nuclear size and estrogen receptor (ER) content by image cytometry. The method, previously used to analyse the proliferation of the breast cancer cell line MCF‐7, was applied here to analyse the growth of this cell line under estradiol (E2), hydroxytamoxifen (OH‐TAM), and both E2 and OH‐TAM treatments. The method extracts characteristic parameters of single nuclei and features that measure the global and local organisation of the cells in their growing phase. Modifications of the heterogeneity of the cell line are emphasised through phenotypic changes and modifications of the spatial organisation of the cells. The hormone (E2) generates a very fast growth of cells with small nuclei that became ER negative in the long term. The antihormone (OH‐TAM) produces a gradual selection of ER negative or poorly positive cells with large nuclei. These modifications are reversed when E2 and OH‐TAM are simultaneously used. Moreover, estradiol induces a permissive context of proliferation, whereas hydroxytamoxifen acts only on some subpopulations. The combination of cell count, cytomorphology, and cell organisation revealed the magnitude of the potential of structuration of hormones or antihormones on in vitro growing cells.